ArcView GIS : GIS - Environmental Systems Research Institute (Redlands, Calif.) (Redlands, Calif. : ESRI, 1996)
Desktop geographic information system for storing, modifying, querying, analyzing, and displaying data. Links with any SQL DBMS, ASCII, dBASE or INFO files. Features Avenue object-oriented programming language. Includes views, editable map legend, feature-based text labels, database queries, synchronous selection environment, multiple map displays, address matching and geocoding, intelligent map redraw, and set of sample data.
Title from disc label.
System requirements: 486 PC; 12MB RAM (17MB virtual memory); MS-DOS 5.0 and Windows 3.1, Windows for Workgroups 3.11, Windows NT 3.51, or Windows 95; VGA graphics display; hard drive; CD-ROM drive; mouse or compatible pointing device.
Keywords: Geographic information systems -- Software; Geographic information systems -- Software